The Analysis of Determinant Factors Intention to Use Video Streaming: Study Case Customer of Goplay - Tengku Kespandiar; Sudarmiatin (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The development of the internet, one of which is in the world of entertainment with the emergence of streaming video on demand (SVOD) services, marks the entry into the era of digitalization 4.0. SVOD is an interactive television service that can be watched via the internet. SVOD is one of the forms of entertainment that is increasingly in demand by the public, especially young people. One of the SVOD services that has recently appeared is GoPlay. GoPlay is an application that provides streaming video on demand services, which is similar to other streaming applications. GoPlay is an application launched from Indonesia that was released by a well-known platform in Indonesia, namely GoJek. However, GoPlay has not been able to compete with several other platforms in terms of the number of users. Broadly speaking, there are several competitors that GoPlay cannot compete with in terms of the number of users, namely Netflix, Disney+ Hotstar, and Viu. This phenomenon explains why this research aims to increase the number of GoPlay application users. There are nine hypotheses to be tested in this study. Data will be analyzed using the Structural Equation Model (SEM) with the SMARTPLS 3.2.9 tool. The results of this study show that compatibility has a positive influence on perceived ease of use, relative advantage has a positive influence on perceived usefulness, accessibility has a positive influence on perceived ease of use, and also perceived ease of use, perceived usefulness, and perceived safety have a positive influence on attitude, while perceived performance risk has a negative influence on attitude. And the results of this study indicate that attitude has a positive influence on the intention to use the GoPlay application.